A radiographic study of the distal femoral epiphysis. (June 2015) - Nguyen, Cynthia V.; Greene, Janelle D.; Cooperman, Daniel R.; Liu, Raymond W.
Purpose: Previous studies have described the complex undulation pattern in the distal femoral physis. We investigated whether standard radiographs can visualize these landmarks, in order to guide hardware placement in the distal immature femur. Methods: We studied 36 cadaveric immature femora in specimens 3 to 18 years of age. Anteroposterior (AP) and lateral radiographs were obtained with and without flexible radiodense markers placed on the major undulations and were analyzed to determine the relative height or depth of each topographical landmark. Intraclass correlation coefficients (ICCs) were calculated between measurements taken with and without markers for each undulation on each view. Results: Examination of the specimens confirmed a central peak and anteromedial and posterolateral valleys as the major physeal structures. AP radiographs without markers correlated well with marked AP radiographs for all three landmarks (ICC = 0.92, 0.92, 0.91), but the lateral radiographs had lower correlations for the posterolateral valley (ICC = 0.36). The correlation between AP and lateral radiographs without markers on the posterolateral valley was also decreased compared to the other two landmarks (ICC = 0.28 versus 0.57 for the central ridge and 0.62 for the anteromedial valley). Conclusions: This is the first study to rigorously evaluate radiographic visibility of the distal femur physeal undulations. The position of the central ridge, anteromedial valley, and posterolateral valley are reliably seen on AP radiographs, while the lateral view is less consistent, especially for the posterolateral valley. We recommend that caution should be taken when placing screws near the posterolateral aspect of the epiphysis, as lateral views do not visualize those undulations well.